Successful use of intra venous tenecteplase for acute ischemic stroke in pregnancy - Balamurugan Namasivayam; Chitra Sengodan; Lavanya Mohanasundaram; Sathya Chinna Gounder; Madunisha Sivakumar (eNeurologicalSci)
Intravenous thrombolysis (IVT) with tenecteplase or alteplase is the standard of care in, patients with Acute Ischemic Stroke (AIS) presenting within 3–4.5 h. However here, are no established guidelines for such treatment during pregnancy. We report a case, of AIS in third trimester of pregnancy successfully treated with Tenecteplase. To the, best of our knowledge, this is the first and only case of acute ischemic stroke in, pregnancy treated with Tenecteplase.